(untitled) (Marketing Journal, 2024)
This research paper presents a quantitative analysis of the marketing challenges in the higher education system of Uzbekistan, focusing on key indicators such as branding, recruitment, and retention. The study utilizes data from various sources, including surveys, official reports, and statistical databases, to identify the magnitude of these challenges and their impact on the system. Based on the analysis, the paper provides recommendations for addressing these challenges and improving the overall effectiveness and competitiveness of the higher education system.